An investigation of saliva and plasma levels of urotensin 2 in recently diagnosed type 2 diabetes mellitus patients on metformin treatment - Gozel, Nevzat; Oral, Kubra; Ozdemir, Fethi Ahmet; Onalan, Erhan; Kuloglu, Tuncay; Aydin, Suleyman; Kilinc, Faruk (Via Medica, 2020)
Introduction: Diabetes mellitus (DM) is a primary disease of the carbohydrate metabolism that is characterised by absolute or relative insulin deficiency, or insulin resistance. Although life expectancy is low for diabetic patients, the prognosis has been improved in recent decades. Metformin is an oral antidiabetic that reduces insulin resistance and plasma glucose levels by decreasing glucose production in the liver. It can be used as a standalone treatment or in combination with other antidiabetic medications or insulin. Urotensin 2 (U-II), which is one of the most effective known vasoconstrictor peptides, was observed to act as a vasoconstrictor in diseases such as hypertension and heart failure, and to induce vasodilation in healthy volunteers. Some studies have proposed that the activation of the U-II system could lead to metabolic syndrome. Certain studies have determined a link between DM and U-II. However, there exist no studies on the effects of U-II in recently diagnosed type 2 DM patients after metformin treatment. This study aims to investigate the plasma and saliva levels of U-II at diagnosis and after a three-month metformin treatment in recently diagnosed type 2 DM patients, and to compare these levels to those of healthy volunteers. Material and methods: Our study compared 30 recently diagnosed type 2 DM patients to their states after three-month metformin treatment and 30 healthy volunteers. Results: When compared with the control group, there was no significant increase in the plasma and saliva U-II levels of recently diagnosed type 2 DM patients. We determined a statistically significant increase in the plasma and saliva ureotensin-2 levels of recently diagnosed type 2 DM patients after a three-month metformin treatment (p < 0.05). Conclusions: It was concluded that the patients with type 2 DM have a multifactorial aetiopathogenesis and an increase in U-II levels after metformin treatment. Metformin has no known effect on the U-II metabolism; therefore, the findings need confirmation through more clinical and experimental studies with more participants.
Keywords: type 2 diabetes mellitus; metformin; urotensin 2